Memories as religion: What can the broken continuity of tradition bring about? − Part two - Urbaniak, Jakub (HTS teologiese studies, 2015)
In postmodern societies the symbolic vacuum, a result of the loss of a unified religious tradition, calls for substitutes in the form of fragmentary and isolated memories. By drawing from the reservoir of those memories in an arbitrary and subjective way, privatised (de- institutionalised) religion creates a kind of symbolic bricolage. Can such a bricolage become more than a mere ‘counterfeit’ of collective meaning that religion once used to provide? Can religious tradition, based on a broken continuity of memory, still bring about a matrix of the ways of expressing one’s faith? If so, how? This twofold study seeks to explore those and similar questions by means of showing, firstly, in what sense religion can be conceived of as memory which produces collective meanings (Part One) and, secondly, what may happen when individualised and absolutised memories alienate themselves from a continuity of tradition, thus beginning to function as a sort of private religion (Part Two). Being the second part of the study in question, this article aims at exploring the postmodern crisis of religious memory, which includes the pluralisation of the channels of the sacred and the differentiation of a total religious memory into a plurality of specialised circles of memory. Firstly, it examines the three main aspects of the current crisis of continuity at large, namely the affirmation of the autonomous individual, the advance of rationalisation, and the process of institutional differentiation. Secondly, the plurality of the channels of the sacred is discussed in light of religion’s apparently unique way of drawing legitimisation from its reference to tradition. This is followed by two illustrations of the reconstruction of religious memory. In the final section of the article, a theological reflection on possible directions that may be taken in the face of the postmodern crisis of religious memory is offered.